Gold Dinar And Silver Dirham, Its Application - Liow, Yoke Woon (2005)
The objective of this paper is to find out how the multinational companies are going to take gold or gold dinar as a payment if they are presented with the option of gold payment. The result showed that these companies are willing to take the gold as a payment seriously if they perceived that this gold system is popularly accepted by the masses as well as if the system is easily transacted.